Performance of MSWI bottom ash under freezing and thawing - Škulteckė, Judita; Vaitkus, Audrius; Šernas, Ovidijus (International Conference “Environmental Engineering”, 2023)
The aim of this paper is to evaluate the performance of municipal solid waste incinerator (MSWI) bottom ash under freezing and thawing and how it disintegrates. For this purpose, three different MSWI bottom ash samples, taken from different periods and waste-to-energy plants, and a reference one, produced only from natural aggregates, were tested according to two test methods: EN 1367-1 and a modified one, where the amount of particles smaller than 0.063 mm was determined after 10 freeze-thaw cycles. The results showed that the MSWI bottom ash is more susceptible to freezing and thawing compared to natural aggregates, but it disintegrates similarly.